Some Physico-Chemical Analyses of Groundwater Sources in Al-Marj Region in the North-East of Libya - Lawgali, Youssef F. (Scientific Journal for Faculty of Science-Sirte University, 2022)
The main aims of this study are to evaluate some Physico-chemical quality of groundwater in Al-Marj city in Libya for drinking, domestic and irrigation uses. All results of the measured physical parameters (Temperature, turbidity, and odor) were within the recommended range by Libyan standards, and WHO guideline values but the chloride (Cl) and ammonia (NH3) concentrations in some sites are exceeded the recommended values by Libyan standard. This is indicating that the potential contamination by municipal sewage or agricultural activity. Most of the groundwater samples were within the recommended value by Libyan standards and WHO guidelines, except one groundwater sample, which was collected from site 6W (sample No.10), in the west direction of Al-Marj city. This groundwater sample recorded the turbidity values 5.85 NTU, and this value was higher than the permissible value by Libyan. The average results for the physical parameters the average of turbidity results was higher than 3.0 NTU at site 6W (sample No.10), and the rest of the physical parameters of the other sectors, were within the recommended range by the Libyan standards in all other sites. The results of the chemical parameters were within the Libyan permissible limits, except the Cl- average levels were higher than the Libyan standard, which were ranged from 256.8 to 372 mg/l in the Eastern and western sectors in the study area. Also, the ammonia was elevated to the Libyan standard in eastern sites which was ranged from 1.66 to 9.72 mg/l.